Biosynthesis of silver nanoparticles with antioxidant activity using Mesona palustris Bl. leaf water extract - Aida, Siti Nor; Kristiningrum, Nia; Retnaningtyas, Yuni - (Jurnal Natural, 2025)
Mesona palustris Bl. has considerable potential. Still, it has yet to be matched by its utilization in nanotechnology, especially nanoparticles (1-100 nm), which have superior physicochemical properties and activities. This laboratory study aims to determine the potential of of Mesona palustris Bl. leaf water extract as a bioreductant and capping agent in the biosynthesis of silver nanoparticles (AgNPs), as well as to evaluate the antioxidant activity of the synthesized AgNPs using the DPPH assay. The biosynthesis method produced optimum AgNPs with a ratio of 1% Mesona palustris Bl. leaf water extract, AgNO3, and dispersing medium 0.75:7:5 (v/v) synthesized for 60 minutes at 55C. The maximum wavelength of AgNPs produced was 433 nm with an absorbance of 0.677. FT-IR spectrophotometric characterization showed that phenolic compounds in the Mesona palustris Bl. leaf water extract is thought to act as a bioreductors and capping agent in the synthesis of AgNPs. SEM results showed that the AgNPs were spherical. Meanwhile, the PSA test results showed the average size of AgNPs was 81 nm, and the polydispersity index was 0.323 (moderately polydispersed). The IC50 value of AgNPs synthesized with Mesona palustris Bl. leaf water extract against DPPH free radicals was 71.501 1.347 g/mL, which is included in the potent antioxidant and better than Mesona palustris Bl. leaf water extract.